MODEL OF COMPETITIVENESS MANAGEMENT OF FUNCTIONAL INDUSTRIAL CLUSTER - E. A. Kukol’Nikova (Russian Journal of Economics and Law)
The article presents the author’s model of compatibility management of functional industrial cluster, and gives results of its stability research and model parameters identification.